Expression of p53 and Bcl2 Mammary Adenocarcinoma in C3H Mice Administered With Salvia miltiorrhizae Bunge root extract - Liza Suryani Dewi; Noor Widjayahadi; Indra Wijaya (Journal of Biomedicine and Translational Research, 2016)
Background: Breast cancer is on the first or second most malignancy in many places around the world. The incidence of breast cancer was increasing, also in Indonesia. Prevention and treatment of breast cancer have not been satisfactory, since patients and medical practitioners are searching for other therapeutic and preventive agents. Salvia miltiorrhizae Bunge roots is one of the therapeutics agent used in traditional medicine have been studied in foreign country.Objective: To prove the p53 and Bcl2 expression in C3H mice mammary adenocarcinoma using multilevel doses of the Salvia miltiorrhizae Bunge roots extract. Methods :The study is a randomized post-test only controlled group design. A total of 18 adenocarcinoma mice, divided into 3 groups. The first group was administered with 60mg/KgBW/day and the second group was given by 180mg/KgBW/day, for 21 days. All mice were terminated on day 22nd. The p53 and Bcl2 expressions were analyzed using Allred score, statistically analized by Kruskal Wallis followed by Post-Hoc Mann Whitney U test.Results :Immunohistochemistry staining shows the p53 expressions have been increased between groups, but Bcl2 were decreased. The Kruskal-Wallis and Post-Hoc Mann Whitney U test are significantly difference between groups.Conclusion :All of the p53 and Bcl2 expressions between groups are significantly differences.